Selection of Tourist Destinations in the Thousand Islands (Kepulauan Seribu) Based on the Preference Value of the Simple Additive Weighting Method - Khasanah, Fata Nidaul Khasanah (IT Journal Research and Development, 2023)
One of the potentials that can improve the economy of local communities is development in the tourism sector. Kepulauan Seribu is an archipelago area in the north of Jakarta, this area has tourism potential in the form of a cluster of islands. This group of islands has different characteristics to be used as a tourist attraction, including marine tourism, historical tourism and nature reserve tourism (conservation). Islands that have historical tourism potential are the reason for conducting research related to the selection of tourist destinations in the Kepulauan Seribu, such as Kelor, Onrust and Cipir island. The obstacles of the community in finding the right tourism potential are still lacking information from the aspects of attractions, accessibility and facilities. To assist tourists in choosing a place, a decision support system is needed that can be completed using the Simple Additive Weighting method. There are five assessment criteria including scenery, photo spots, transportation, toilets and places to eat/resto. Determination of weights on criteria using a statistical approach from the questionnaire results. The result of the preferred tourist recommendation preference value is the island of Kelor because there are seven highest scores obtained by the island compared to Onrust and Cipir island.